Polarization, Shifting Borders and Liquid Governance
XVII, 427 p. 18 illus., 5 illus. in color.
Keywords: This open-access book explores the security dynamics amid the polarization, shifting borders, and liquid governance that define the Zeitenwende era in Europe's eastern neighbourhood and Central Asia. Presenting various case studies, the volume unveils the intricate web of border dynamics and practices, including the nuanced interplay of border disputes within the Organization for Security and Cooperation in Europe (OSCE) member states. The contributions shed new light on how contested borders and liquid modes of governance have impacted the engagement of international organizations such as the European Union (EU), North Atlantic Treaty Organization (NATO), and OSCE in security crises and conflict prevention. Delving deeper, a special part dissects the ongoing Russia-Ukraine conflict and examines European and international responses. By analyzing the stances of diverse European countries, their neighborhood, and international organizations, this section uncovers commonalities and disparities in their approaches to the Ukrainian crisis.